The Nexus Between Financial Stability and Economic Growth in Southeast Asia - Kenedi, Kenedi (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractFinancial stability is an important part of economic growth. The main objective of this study is to analyse how financial stability (using Bank Z-Score) affects economic growth. The data used is country-level data from five selected Southeast Asian countries (Indonesia, Cambodia, Malaysia, Philippines, and Thailand) for the period 2011 – 2021 using the ARDL model approach. The results of this study found strong evidence that financial stability (banking stability) has a positive effect on economic growth for countries in the Southeast Asian region. This study also reveals that it is not only important financial stability variables to achieve economic growth, but investment and trade openness must also be increased if the country is to achieve its expected economic growth. A positive correlation between investment and trade openness suggests a potential for these factors to contribute to economic growth synergistically. Keywords:Financial Stability, Economic Growth, Bank Z-Score, ARDL